2019
DOI: 10.1089/hum.2018.098
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Seroprevalence of Antibodies Against AAV-LK03 in a UK Population Cohort

Abstract: Recombinant adeno-associated virus (rAAV) vectors are a promising platform for in vivo gene therapy. The presence of neutralizing antibodies (Nab) against AAV capsids decreases cell transduction efficiency and is a common exclusion criterion for participation in clinical trials. Novel engineered capsids are being generated to improve gene delivery to the target cells and facilitate success of clinical trials; however, the prevalence of antibodies against such capsids remains largely unknown. We therefore asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…Using the luciferase-based neutralizing antibody detection assay, and a cutoff of 1:5, the seroprevalence to WT AAV3B in our cohort of 100 individual serum samples was 37%. This was very similar to the 35% previously reported for a UK patient population 54 and 36% for a North American population 55 respectively. In a separate study, we analyzed a similar number of North American patient samples and found a seroprevalence to AAV3B of 45% (I.Z., unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…Using the luciferase-based neutralizing antibody detection assay, and a cutoff of 1:5, the seroprevalence to WT AAV3B in our cohort of 100 individual serum samples was 37%. This was very similar to the 35% previously reported for a UK patient population 54 and 36% for a North American population 55 respectively. In a separate study, we analyzed a similar number of North American patient samples and found a seroprevalence to AAV3B of 45% (I.Z., unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…Although AAV seroprevalence varies geographically, neutralizing antibodies (NAbs) that recognize virtually all AAV serotypes can be found in a large proportion of the human population (ranging from 30 to 60%). Successive infections may explain the high prevalence of anti-AAV NAbs in humans (37)(38)(39), resulting in broad cross-reactivity across AAV serotypes of different origins, including human, mammalian or engineered. Regardless of the geographic region, the most prevalent NAbs are directed against AAV2, followed by AAV1 (38).…”
Section: Humoral Immunity To Aavmentioning
confidence: 99%
“…We screened 24 rhesus macaques (4-10 years of age) for absence of pre-existing serum neutralizing antibodies (NAbs) to AAV8 using an in vitro transduction inhibition assay, 47 and identified 6 animals (mean age, 8.3 ± 2.4 years; 3 males/3 females) with no detectable NAbs (<1:2,560), consistent with the high prevalence of anti-AAV8 NAbs reported in rhesus macaques. 48 We injected both eyes of three of these animals with nonhuman primate-grade AAV8 expressing enhanced green fluorescent protein (GFP) under a ubiquitous cytomegalovirus (CMV) promoter at two different doses (7 Â 10 11 or 7 Â 10 12 vector genomes [vg]/eye) using a 700-mm-long 30-gauge microneedle ( Figure 1B, Clearside Biomedical, Alpharetta, GA, USA) inserted through the conjunctiva and sclera into the suprachoroidal space in the superotemporal quadrant (single 100-mL injection) of left eyes, and both superotemporal and inferonasal quadrants (two 50-mL injections) of right eyes ( Figure 1C). No surgical microscope or vitrectomy surgery was required.…”
Section: Suprachoroidal Aav8 Transduction Is Diffuse Peripheral Andmentioning
confidence: 99%